PRIVATE BUSINESS COACHING IN MALAYSIA: A CALL FOR BETTER REGULATION - Ahmad Syahmi Ahmad Fadzil; Rusnani Mohamad Khalid; Zulhazmi Yusof; Amir Imran Zainoddin (International Journal of Accounting, Finance and Business, 2022)
The services of business coaching are being made widely available to small and medium-sized enterprises (SMEs) through the mass media. Business coaching is claimed can enhance the SMEs business performance in many ways. Although the subjective benefits were said to be many, there is hardly any quantitative reported evident on the outcome of such services to SMEs. Additionally, although there has been much research conducted on business coaching and mentoring, our understanding on the effect of private business coaching is still at nascent stage along with its regulations. This research utilized secondary data gained from scientific database analysis from Google Scholar, Scopus and websites from consumers’ association, pandemic related news, not-for-profit international association and government agencies that are related to the theme of the research. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is adopted to better identify the trend of business coaching. Findings found that there are divergent views of business coaching but ultimately, majority of the scholars agreed that this business coaching has an immensely promising future. Two recommendations were made to enhance the regulation through monitoring and accreditation. Future research should be conducted via empirical basis to further validate the effect and benefit of business coaching which could be either narration; positive or negative. This paper has provided additional insight on the development of business coaching on SMEs in Malaysia. Additionally, it also updates the knowledge and discussion in this domain that can provide insight to policy makers and other beneficiaries.